Bhinna jaṇe Bibekānanda - Dāsa, Cittarañjana (Inṣṭityuṭa aph Orieṇṭāla eṇḍ Oriśān Ṣṭaḍij, Di' Ẏunibharsa, 1995)
Study on the social and political views of Swami Vivekananda, 1863-1902, after his return from United States